Antenatal Multimodal Intervention and Hemodynamic Response in Pregnant Women who Experience Back Pain - Wahyuni, Sri; Rahayu, Tutik; Distinarista, Hernandia; Wuriningsih, Apriliyani Yulianti (International Journal of Psychosocial Rehabilitation, 2020)
Pregnancy is a physiological process experienced by a woman which gives rise to an adaptation response to the body that often causes complaints. The study aimed to determine the effectiveness of multimodal antenatal interventions for back pain and hemodynamic responses in pregnant women. This study used a Quasy Experimental design with a pre and posttest with a control group design. Data were collected using a Numeric Rating Scale and observation sheet. The number of samples, 76, consisting of 38 in group 1 and 38 in group 2, were taken by purposive sampling technique. The data obtained were processed using the Wilcoxon test and the Mann–Whitney U-Test. There is an influence between Antenatal Multimodal Interventions in the form of exercise and acupressure on pain, and hemodynamic response, with p <0.05. There is a relationship between the use of maternity belts and pain, but there is no effect on the hemodynamic response. Conclusion, Multimodal Antenatal Intervention is more effective in reducing back pain and stabilizing the hemodynamic response in pregnant women compared to the use of maternity belts.